Industry 4.0 adoption and firm efficiency: evidence from emerging Giants in Asia Pacific region - Rehman, Saif Ur (Brazilian Journal of Operations & Production Management, 2023)
Purpose - Industry 4.0 links smart production processes with embedded system production technologies to open the door to a new technological era that fundamentally alters industry value chains and business structures. This study examines the effects of Industry 4.0 on firm efficiency. Methods - Based on a cross-country sample of 1440 firms operating in the top twelve Giants of Asia-Pacific countries and a control sample with another set of 1440 similar-sized firms from non-adopting firms. Findings - The empirical evidence shows that Industry 4.0 positively impacts firm efficiency. Next, the Tobit model is used for the robustness of the main findings. Further, study also examine the mediating role of intangible assets (human capital and firm reputation) for the impact of Industry 4.0 on firm efficiency. Study findings support the hypotheses that intangible assets mediate the Industry 4.0-firm efficiency relationship. Implications - Study findings have managerial implications for production and operation managers on enhancing firm efficiency. Drawing upon practice-based-view theory, this study is the first to explore the mediating role of intangible assets (human capital and firm reputation) between in-Industry 4.0 and firm performance. Originality - This study shed light on the significance of intangible asset congruence in enhancing Industry 4.0 impact.